IMPLEMENTASI ASUHAN KEPERAWATAN DAN INTERVENSI FENOBARBITAL PADA NEONATUS DENGAN KEJANG - Ribka Elfrida; Ditte Ayu (Ensiklopedia Research and Community Service Review, 2025)
Neonatal seizures are a critical neurological emergency requiring swift and appropriate management to prevent long-term neurodevelopmental sequelae. This study addresses the urgency of specialized nursing care combined with optimal pharmacological intervention for neonates experiencing seizures. The research employed a descriptive case study methodology, focusing on Nursing Care for Patient D diagnosed with neonatal seizures one of the hospital in Batam. Data were collected through observation, physical examination, and documentation analysis, particularly evaluating the effectiveness of phenobarbital therapy in controlling seizure recurrence. The findings indicate that comprehensive nursing intervention, including careful monitoring and timely administration of phenobarbital, significantly reduced the frequency and intensity of seizure episodes and improved neurological stability. This case highlights the crucial role of collaborative care between nursing staff and medical teams in achieving favorable outcomes for high-risk neonates, emphasizing the need for robust institutional protocolsKeywords: Neonatal seizures; Nursing care; Phenobarbital therapy; Seizure recurrence; Collaborative care